Insulin signaling genes modulate nicotine-induced behavioral responses in Caenorhabditis elegans. Issue 1 (February 2016) - Wescott, Seth A.; Ronan, Elizabeth A.; Xu, X.Z. Shawn
Abstract : Insulin signaling has been suggested to modulate nicotine dependence, but the underlying genetic evidence has been lacking. Here, we used the nematode, Caenorhabditis elegans, to investigate whether genetic alterations in the insulin signaling pathway affect behavioral responses to nicotine. For this, we challenged drug-naive C. elegans with an acute dose of nicotine (100 μmol/l) while recording changes in their locomotion speed. Although nicotine treatment stimulated locomotion speed in wild-type C. elegans, the same treatment reduced locomotion speed in mutants defective in insulin signaling. This phenotype could be suppressed by mutations in daf-16, a gene encoding a FOXO transcription factor that acts downstream of insulin signaling. Our data suggest that insulin signaling genes, daf-2, age-1, pdk-1, akt-1, and akt-2, modulate behavioral responses to nicotine in C. elegans, indicating a genetic link between nicotine behavior and insulin signaling.